2011
DOI: 10.1038/nri2975
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in innate immune responses

Abstract: The innate immune system has a key role in the mammalian immune response. Recent research has demonstrated that mitochondria participate in a broad range of innate immune pathways, functioning as signalling platforms and contributing to effector responses. In addition to regulating antiviral signalling, mounting evidence suggests that mitochondria facilitate antibacterial immunity by generating reactive oxygen species and contribute to innate immune activation following cellular damage and stress. Therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
977
1
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,128 publications
(1,011 citation statements)
references
References 102 publications
19
977
1
14
Order By: Relevance
“…These metabolic pathways traced to mitochondria. Mitochondria are responsible for initiating and coordinating innate immunity18 and produce stereotyped changes in oxidative metabolism under stress19 that lead to the regulated release of purine and pyrimidine nucleotides like ATP and UTP through cell membrane channels 20. Inside the cell, ATP is an energy carrier.…”
Section: Introductionmentioning
confidence: 99%
“…These metabolic pathways traced to mitochondria. Mitochondria are responsible for initiating and coordinating innate immunity18 and produce stereotyped changes in oxidative metabolism under stress19 that lead to the regulated release of purine and pyrimidine nucleotides like ATP and UTP through cell membrane channels 20. Inside the cell, ATP is an energy carrier.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has demonstrated that mitochondria participate in a broad range of innate immune pathways, such as the regulation of antiviral signaling and antibacterial immunity, ROS production, autophagy, and cell death. 50 Therefore, it will be interesting to investigate the role of GM-M in host defense against bacterial, viral, and fungal infections in the future.…”
Section: Dv-induced Inflammasome Activation Is Via Clec5amentioning
confidence: 99%
“…Late phagosomes acquire markers such as the lysosomal-associated membrane proteins (LAMP)-1 and -2, which are required for acquisition of Rab7 (9) and of microbicidal properties (10). Crucial to the killing of many intracellular pathogens is the generation of reactive oxygen species (ROS) in the phagosome, which is produced mostly by the NADPH oxidase 2 complex (NOX2) (11,12) and mitochondria (13). The complex, which is normally inactive in the cell, is constituted by six subunits.…”
mentioning
confidence: 99%